Housing and housing politics in European metropolises. Jahrbuch StadtRegion 2017/2018. - (:unkn) unknown (Springer VS, 2019)
Neoliberal paradigms and the privatisation of housing have recently been confronted with social movements in many large European metropolises. The political and social need for more participation in housing, for new forms of urban land politics and for specific and powerful rental regulation is obvious. The special book section analyses these dimensions of housing and housing politics in a comparative European perspective and discusses new policy approaches for urban housing. Furthermore, the Jahrbuch StadtRegion offers scientific articles and reports, as well as a monitoring section and book reviews related to interdisciplinary urban research and planning issues.
Keywords: Stadt; Stadtregion; Metropole; Metropolregion; Wohnungsbedarf; Wohnungsversorgung; Wohnungsmarkt; Immobilienmarkt; Kommunale Wohnungspolitik; Wohnungspolitik; Internationaler Vergleich